Review of challenges and opportunities in promoting Good Dairy Farming Practices - Ponnusamy, Kuppusamy; Lal, Sudhanand Prasad (Indian Journal of Dairy Science, 2015)
This paper reviews ongoing practices in dairy production among different stakeholders and suggests plausible solutions for enhancing the adoption of Good Dairy Farming Practices (GDFP).Â GDFPs were initially conceptualized by FAO and IDF in 2004 and later comprehended in 2011. GDFP is emerging as a viable option for producers to produce safe and healthy milk in tune with specified standards and practices. India being the place of small scale producers has both limitations and opportunities to produce milk as per growing consumer demand. Number of private players, corporate houses, NGOs and research organizations experimented and evolved good practices and approaches which can be easily emulated by other interested stakeholders for production of high quality healthy milk and milk products. Rechristening the role of various organizations along with policies and programmes would pave the way for sustainable dairy production, processing and marketing through adoption of GDFP.Â Â